Gynecological morbidity and treatment-seeking among older adult (aged 45-59) women in India - Manas Ranjan Pradhan; Sourav Mondal; Prasanna Kumar Mudi (BMC, 2023)
Abstract Background Women's gynecological health needs are not limited to the reproductive years of their life. Women are at risk of hormonal changes, gynecological malignancies, and various genitourinary conditions as they move toward menopause and beyond. Concerns about older women's sexual and reproductive health and rights (SRHR) continue to be taboo in many countries, of little interest to researchers and professionals in the field of healthcare, and a "blind spot" in discussions about policy as a whole. Despite the widespread agreement, the life course approach to addressing SRHR concerns has received minimal attention. The study estimates the prevalence, assesses the correlates, and treatment-seeking of gynecological morbidity (GM) among older adult women aged 45-59 years (N = 18,547) in India. Method The analysis was based on the nationally representative Longitudinal Ageing Study (2016-2017) data that adopted a multistage stratified area probability cluster sampling to select respondents. The outcome variables used in this analysis were 'had any GM' and 'sought treatment for any GM.' Women with any morbidity such as per vaginal bleeding, foul-smelling vaginal discharge, uterus prolapses, mood swings/irritability, fibroid/cyst, and dry vagina causing painful intercourse were considered to have any GM. Of the respondents with GM, who sought a doctor's consultation or treatment were considered 'sought treatment for any GM.' Binary logistic regression was conducted to examine the adjusted effect of socioeconomic and demographic predictors of GM and treatment-seeking. Stata (V 16) was used for statistical analyses with a 5% significance level. Results Fifteen percent of the women had any GM, and only 41% of them sought treatment. Age, marital status, education, number of pregnancies, hysterectomy, involvement in household decision-making, social group, religion, wealth status, and region were significantly associated with GM. The odds of treatment-seeking were higher among women with 10+ years of schooling (OR 1.66, CI 1.23, 2.23), with hysterectomy (OR 7.36, CI 5.92, 9.14), with five-plus pregnancies (OR 1.25, CI 0.96, 1.64), and those from the richest (OR 1.91, CI 1.40, 2.60) households than their respective counterparts. Conclusion Many older adult women experience GM, and treatment-seeking is inadequate. The GM prevalence and treatment-seeking vary considerably by socioeconomic and demographic characteristics. Results suggest community-level awareness generation and the inclusion of this otherwise ignored group in programs targeting better health and wellbeing of women.